2005
DOI: 10.1182/blood-2004-05-1714
|View full text |Cite
|
Sign up to set email alerts
|

ICAM-1 recycling in endothelial cells: a novel pathway for sustained intracellular delivery and prolonged effects of drugs

Abstract: IntroductionIntercellular adhesion molecule-1 (ICAM-1) is an Ig family transmembrane glycoprotein constitutively exposed on the luminal surface of endothelial cells (ECs). 1-3 ICAM-1 represents an attractive target for drug delivery to ECs, since it is up-regulated and functionally involved in vascular inflammation, oxidant stress, and thrombosis. [4][5][6][7] Antibodies to ICAM-1 are being explored as therapeutics and affinity carriers in cell cultures, animal models, and early clinical studies. [8][9][10][11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
234
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 128 publications
(254 citation statements)
references
References 57 publications
18
234
1
Order By: Relevance
“…Then, the co-localization of nanoparticles within Lysotracker-labeled cellular compartments was determined. The results were confirmed by labeling lysosomes with Texas Red dextran (10,000 kDa) following a similar protocol (7,29).…”
Section: Intracellular Trafficking Of Nanoparticlesmentioning
confidence: 73%
“…Then, the co-localization of nanoparticles within Lysotracker-labeled cellular compartments was determined. The results were confirmed by labeling lysosomes with Texas Red dextran (10,000 kDa) following a similar protocol (7,29).…”
Section: Intracellular Trafficking Of Nanoparticlesmentioning
confidence: 73%
“…We tested distribution of the radiolabeled TM antibodies and GOX conjugates one hour after IV injection. Previous studies of immunotargeting of radiolabeled conjugates directed to highly accessible endothelial determinants such as TM, angiotensin-converting enzyme (ACE), PECAM-1, intercellular adhesion molecule 1 (ICAM-1) and GP90 showed that their maximum uptake in the lungs occurs within 15-30 min, followed by a short 15-30 min stable period and subsequent reduction of the pulmonary level observed at times more than one hour after IV injection [22,25,27,[46][47][48][49][50][51][52]. Therefore, the kinetics of lung edema development showing a maximum 4 hour after injection of a lower dose of the conjugate selected to avoid overt early lethality (Fig.4C) is not due to delayed accumulation of GOX in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were seeded onto 12-mm 2 gelatin-coated coverslips in 24-well plates and were treated overnight with TNF-␣ before experiments. TNF-␣ treatment upregulates ICAM-1 expression; therefore, it enhances anti-ICAM/NC binding to HUVEC, yet it does not affect their internalization kinetics or trafficking (37,41).…”
Section: Methodsmentioning
confidence: 99%
“…Internalization of anti-CAM/NC occurs via a common pathway, CAM endocytosis, in a variety of CAM-positive cell types (22,36,37,40,41). Human umbilical vein EC (HUVEC) and an endothelial-like cell line, EAhy926 (13), were selected to study the uptake and trafficking of anti-ICAM/NC since they provided insights that have subsequently correlated with in vivo models for endothelial targeting of anti-ICAM/NC (37). HUVEC (Clonetics, San Diego, CA) and EAhy926 were cultured at 37°C, 5% CO 2, and 95% relative humidity in supplemented medium 199 or DMEM (GIBCO-BRL, Grand Island, NY), respectively (36).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation